Cooperative Decision-Making for Drone Swarms - Giacomossi Jr., Luiz; Maximo, Marcos R. O. A.; Brancalion, José F. B. (Anais Estendidos do Simpósio Brasileiro de Robótica e Simpósio Latino-Americano de Robótica (SBR/LARS), 2023)
Unmanned Aerial Vehicles (UAVs) are being researched for their potential in applications like search and rescue, and defense missions. The goal is to enhance the intelligence, communication, and strategic organization. Decision-making techniques enable intelligent UAV decisions, freeing human commanders to focus on higher-level decisions. This research focuses on defense and search and rescue scenarios, and combines AI-based decision-making with UAVs. The study analyze the Loyal Wingman concept in a defense scenario. Also, we propose a solution for a drone swarm to cooperatively search for people in a rescue scenario. Our results demonstrate the effectiveness of distributed decision-making methods in solving problems in both scenarios.